Comparative Study of Captopril Gel Assisted Clean Intermittent Self-Catheterization Versus Xylocaine Gel in Preventing Recurrence of Urethral Stricture Following Direct Vision Internal Urethrotomy - Irfan Ul Haq, Shams Ul Islam, Muhammad Safdar Khan, Sarmad Imtiaz, Muhammad Asif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Direct vision internal Urethrotomy (DVIU) is normally performed technique for the dealing with urethral strictures. Clean discontinuous self-catheterization (CISC) is performed to defeat repeat after DVIU alongside a few antifibrotic specialists to defer the fibrotic procedure. Aim: To compare the effectiveness of captopril gel assisted clean intermittent self-catheterization versus xylocaine gel in preventing recurrence of urethral stricture following direct vision internal urethrotomy. Setting: 84 patients were incorporated into this randomized controlled preliminary at Department of urology, Mayo Hospital, Lahore for a half year. Methods: Patients were haphazardly separated into two gatherings, each gathering containing 42 patients as Group A (CISC with xylocaine gel) and Group B (CISC with xylocaine gel + captopril gel). All patients experienced direct visual inside urethrotomy (DVIU). Following DVIU, the patients performed clean irregular self-catheterization (CISC) according to convention of gathering An and B with 16 french nelaton catheter. The routine was decreased over a 3 months' time frame. Tolerant were for repeat of stricture toward the finish of first, second and third months. Results: Mean length of urethral stricture in Group A was 1.27+ 0.12 and 1. + 0.73 in Group B. Group B had higher success rate in preventing recurrence of urethral stricture with 73.8% patient did not have precedence of stricture as compared to Group A where 42.9% patient had no recurrence. (p value 0.004). Conclusion: Captopril gel assisted clean intermittent self-catheterization is superior to xylocaine gel alone in avoiding recurrence of urethral stricture following direct vision internal Urethrotomy. Keywords: Urethral stricture, clean intermittent self-catheterization (CISC), Direct Visual internal Urethrotomy (DVIU)